Reflecting on self-care practices during clinical psychology training and beyond. Issue 3 (4th May 2017) - Bettney, Laura
Abstract: In this paper, I will discuss the concept of self-care and its importance for clinical psychologists, both during training and post-qualification. I will review the pertinent literature in this area covering the concept of self-care and its meaning, the personal and professional impact of a lack of self-care for clinical psychologists, and discuss some of the barriers to implementing self-care practices. Throughout the discussion of barriers to self-care, I will intersperse three reflective pieces on my own experiences throughout clinical psychology training, which will allow for a more in-depth exploration of the issues. My conclusion will highlight the personal, professional and systemic barriers to self-care in clinical psychologists, and in other helping professionals, and suggest possible ways of tackling these barriers and promoting greater utilisation of self-care during clinical training and beyond and across different professional groups.